Multiscale biased chemical space remodeling for developing APLNR agonists with anti-HFpEF efficacy - Qiu Sun; Xiaowen Tian; Lun Tan; Yan Deng; Sicen Liu; Yixiao Xiong; Yuying Feng; Yujia Wang; Lele Zhang; Jiayi Zhu; Huan Xiao; Zhenhua Shao; et al. (Proceedings of the National Academy of Sciences, 2025)
Heart failure with preserved ejection fraction (HFpEF) represents a significant global health burden, yet effective pharmacotherapies remain elusive. The angiotensin-like 1 receptor, also known as the apelin receptor (APLNR), is a promising target for treating HFpEF due to its role in modulating cardiovascular function. Despite the cardioprotective effects of endogenous ligand, apelin, achieving G-protein-biased agonism for therapeutic benefit poses a significant challenge. In this study, we unravel the biased signal transduction pathway mediated by a reported partial G i -protein-biased APLNR agonist CMF-019 and developed a biased chemical space remodeling approach to identify exclusive G-protein-biased agonists targeting APLNR. These agonists exhibited enhanced Gi-protein-biased function and protective effects in both in vitro and in vivo. Our findings not only enhance comprehension of APLNR-biased agonism but also establish drug design strategies for modifying and reshaping biased chemical landscapes in other G-protein-coupled receptors (GPCRs).